Tissue Drug Concentrations of Anti-tumor Necrosis Factor Agents Are Associated with the Long-term Outcome of Patients with Crohn's Disease. Issue 12 (December 2017) - Yoshihara, Takeo; Shinzaki, Shinichiro; Kawai, Shoichiro; Fujii, Hironobu; Iwatani, Shuko; Yamaguchi, Toshio; Araki, Manabu; Hiyama, Satoshi; Inoue, Takahiro; Hayashi, Yoshito; Watabe, Kenji; Iijima, Hideki; et al.
Abstract : Background: Many reports indicate that a high-serum trough level of anti-tumor necrosis factor (TNF) agents is required for sustained remission in patients with Crohn's disease The pharmacokinetics of anti-TNF agents in inflamed intestinal tissue, however, is not well investigated. We investigated the association between the tissue concentration of anti-TNF agents and long-term disease outcome. Methods: This was a prospective single-center study that enrolled 25 patients with Crohn's disease who were administered infliximab or adalimumab. All participants underwent endoscopy 2 weeks after administration of the anti-TNF agents, and biopsy samples were obtained from both inflamed and noninflamed intestinal tissue. Tissue concentrations of anti-TNF agents were evaluated and the correlation with serum trough levels was compared. The relation between the tissue drug concentration and clinical course over 24 months was also investigated. Results: Concentrations of anti-TNF agents were significantly higher in inflamed tissue than in noninflamed tissue. Patients with high-serum trough concentrations of anti-TNF agents had significantly higher drug levels in the noninflamed tissue than those with low-serum trough concentrations, but no difference in the levels was detected in the inflamed tissue. Patients with high-drug levels in the noninflamed tissue had a significantly higher sustained response rate than patients with low-drug levels. Conclusions: Concentrations of anti-TNF agents in the noninflamed tissue can reflect sustained remission and may be a useful biomarker for monitoring therapeutic intensity in patients with Crohn's disease treated with anti-TNF agents (see Video Abstract, Supplemental Digital Content 1, http://links.lww.com/IBD/B623 ). Abstract : Article first published online 22 September 2017.Supplemental Digital Content is Available in the Text.